2019
DOI: 10.1016/j.newideapsych.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Approach, avoidance, and the detection of conflict in the development of behavioral inhibition

Abstract: Motivation has played an integral role in understanding personality development. Two motivational systems, one associated with seeking reward (approach motivation) and one associated with avoidance of threat (avoidance motivation), have been theorized to represent individual differences in behavioral responses to the environment. However, contextual factors, particularly those with a high degree of novelty, ambiguity, and unpredictability, may simultaneously activate both systems, thereby causing approach-avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 176 publications
(273 reference statements)
1
41
0
3
Order By: Relevance
“…Anxiety was defined as a more complex parameter 60 that in our case reflects both the stress level and the difference in reward between the two stimuli. We presumed that the need to choose between two stimuli with similar values will create a motivational conflict and increase the anxiety level of the subject, in accordance with multiple studies associating motivational conflict and uncertainty with anxiety 27,28,61 . In contrast, a strong difference between the stimuli will solve the conflict and reduce the subject's anxiety.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Anxiety was defined as a more complex parameter 60 that in our case reflects both the stress level and the difference in reward between the two stimuli. We presumed that the need to choose between two stimuli with similar values will create a motivational conflict and increase the anxiety level of the subject, in accordance with multiple studies associating motivational conflict and uncertainty with anxiety 27,28,61 . In contrast, a strong difference between the stimuli will solve the conflict and reduce the subject's anxiety.…”
Section: Discussionmentioning
confidence: 78%
“…In our model, anxiety was defined as a product of two variables: the stress level, assumed by us to be directly related to the novel environment, thus continually decreasing during the test due to habituation, and the difference in reward between the two stimuli. In other words, the smaller the difference in reward between the stimuli, the higher the anxiety level of the subject, due to the difficulty of choosing between the two competing stimuli, which creates a motivational conflict 27,28 . In this model, the only difference between C57BL/6J mice and SD rats was the dynamics of social reward, with SD rats showing an initial high level of social reward, which gradually decreased during the test, and C57BL/6J mice showing an initial low level, which gradually increased.…”
Section: Resultsmentioning
confidence: 99%
“…Previous conflict works have shown that DZPM increases: time spent in the open arms of elevated plus maze ( Rex et al, 1996 ; Chaouloff et al, 1997 ; Dalvi and Rodgers, 1999 ), time spent at the center of an open field that includes food ( Britton and Britton, 1981 ; Bodnoff et al, 1989 ; Rex et al, 1996 ), time spent in an illuminated but not a dark compartment ( Chaouloff et al, 1997 ), foraging behavior ( Walters et al, 2019 ), as well as increased rates of punished reward responding ( Vogel et al, 1971 ; Paterson and Hanania, 2010 ) and conditioned suppression during conflict ( Kilts et al, 1981 ; Commissaris and Rech, 1982 ). Engaging in a situation that is simultaneously threatening and rewarding leads to increased physiological arousal ( Barker et al, 2019 ), which may represent an aversive signal ( Dreisbach and Fischer, 2012 ) and thereby induce anxiety. Thus, previous results along with our present findings using conflict tests are consistent with the notion that DZPM may reduce the inability to engage in reward-seeking behaviors (reduce behavioral inhibition) possibly by reducing the increase in arousal that is associated with conflict (“anticonflict effect”) ( Liljequist and Engel, 1984 ; Pericic and Pivac, 1996 ; Rowlett et al, 2006 ), thereby allowing the individual to reach their goal.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this theorized relationship, there are inconsistencies within the literature on threat sensitivity and frontal asymmetry. Some work has found that those with greater threat sensitivity— or related constructs such as shyness and behavioral inhibition (characterized by avoidant coping styles and attentional bias to threat; Barker et al, 2019 ; Perez-Edgar and Fox, 2005 )— have greater right frontal asymmetry ( Poole et al, 2018 ; Sutton and Davidson, 1997 ; Wacker et al, 2009 ). Other studies, however, have found no relationship ( Amodio et al, 2008 ; Coan and Allen, 2003 ; Harmon-Jones and Allen, 1997 ; Hewig et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%